2017
DOI: 10.18494/sam.2017.1634
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuous Measurement of Mite Allergen (Der f 2) Using a Surface Acoustic Wave Immunosensor under Moderate pH for Long Sensor Lifetime

Abstract: In this work, we developed a surface-acoustic-wave (SAW)-based immunosensor for the monitoring of house dust mite (HDM) allergen, Dermatophagoides farinae group 2 (Der f 2). The SAW immunosensor was fabricated by modifying the sensor surface with a self-assembled monolayer of ORLA85 protein and immobilized capture antibodies (cAb) for Der f 2. Because of the pH-insensitive property of ORLA85, the sensor surface could be used for successive measurement and regeneration of the sensor surface. In experiments, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The same research group also fabricated a SAW-based immunosensor for the detection of D. farinae group 2 allergens (Der f 2). 78 A sensor was fabricated by 79 This microfluidic immunosensor achieved an LOD of 1 and 10 pg/mL with a spectrometer and cell phone camera as an optical detector, respectively. The experiment comprised sampling over 30 s and microfluidic detection over 5 min.…”
Section: ■ Immunosensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same research group also fabricated a SAW-based immunosensor for the detection of D. farinae group 2 allergens (Der f 2). 78 A sensor was fabricated by 79 This microfluidic immunosensor achieved an LOD of 1 and 10 pg/mL with a spectrometer and cell phone camera as an optical detector, respectively. The experiment comprised sampling over 30 s and microfluidic detection over 5 min.…”
Section: ■ Immunosensing Methodsmentioning
confidence: 99%
“…This exhibited high reproducibility for certain targets with a few residual molecules after regeneration to facilitate the extended use of the sensor as well. The same research group also fabricated a SAW-based immunosensor for the detection of D. farinae group 2 allergens ( Der f 2 ) . A sensor was fabricated by modifying the probe surface with a self-assembled monolayer of ORLA85 protein and immobilized capture antibodies (cAb) for Der f 2 .…”
Section: Immunosensing Methodsmentioning
confidence: 99%
“…This result, showing that the strongest binding between protein G and IgG occurred under a slightly acidic condition, agrees with previous studies. (19,20,28) The dependence of the binding on the mIgG concentration was investigated, and it was found that more binding occurred with increasing concentration [see Fig. 3(c)].…”
Section: Optimizations Of Spr Immunosensormentioning
confidence: 99%
“…Previously, we developed a surface-acoustic-wave-based reusable immunosensor for the semicontinuous measurement of mite allergens. (19)(20)(21) The sensor utilized a highly stable protein to anchor capture antibodies. This surface modification allowed repeated measurement of mite allergens with high reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Qorvo Biotechnologies has obtained an emergency use authorization (EUA) from the FDA for the rapid detection of the COVID-19 antigen by using BAW at the point of care [ 22 ]. On the other hand, SH-SAW sensors are popular in liquid phase applications [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In addition, a unique SH-SAW biosensor system has been commercialized for medical applications.…”
Section: Introductionmentioning
confidence: 99%